Analysis of slope stability using finite element method - Mohd Yusri, Bin Suratman (Universiti Malaysia Sarawak, UNIMAS, 2009)
Slope can be defined as an exposed ground surface that stands at an angle with the horizontal surface. There is several traditional limit equilibrium methods developed for checking safety factor of a slope. These methods, in general, require the soil mass to be divided into slices. The direction of the forces acting on each slice in the slope are assumed. This assumption is a key role in distinguishing one limit equilibrium method from another.